ʺМ’яка силаʺ як інструмент зовнішньої політики Республіки Корея - Лісянська, Валерія Олександрівна; Lisyanska, V. (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Робота присвячена комплексному дослідженню використання інструментів «м'якої сили» у формуванні та реалізації зовнішньої політики Республіки Корея. Розглянуто теоретичні засади концепції «м'якої сили» в системі міжнародних відносин, уточнено понятійно-категоріальний апарат дослідження. Проаналізовано соціально-економічний та політичний профіль країни, особливості її зовнішньоекономічної діяльності та дипломатичних зв'язків у регіональному та глобальному вимірах. Досліджено становлення та еволюцію південнокорейської стратегії «м'якої сили», її інституційне забезпечення та механізми реалізації. Визначено роль культурної дипломатії, зокрема феномену «корейської хвилі» (Hallyu), у просуванні національних інтересів Республіки Корея. Проаналізовано вплив корейських культурних продуктів (K-pop, K-drama, корейського кінематографу) на формування позитивного іміджу країни. Досліджено освітні ініціативи, програми академічних обмінів та діяльність Інститутів Седжонг як важливих компонентів південнокорейської «м'якої сили».

The article is devoted to a comprehensive study of the use of “soft power” instruments in the formation and implementation of the foreign policy of the Republic of Korea. The theoretical foundations of the concept of soft power in the system of international relations are considered, the conceptual and categorical apparatus of the study is clarified. The author analyses the socio-economic and political profile of the country, peculiarities of its foreign economic activity and diplomatic relations in the regional and global dimensions. The formation and evolution of South Korea's “soft power” strategy, its institutional support and implementation mechanisms are studied. The role of cultural diplomacy, in particular the phenomenon of the “Korean wave” (Hallyu), in promoting the national interests of the Republic of Korea is determined. The influence of Korean cultural products (K-pop, K-drama, Korean cinema) on the formation of a positive image of the country is analysed. Educational initiatives, academic exchange programmes and activities of the Sejong Institutes as important components of South Korean “soft power" are studied.
"Soft power" as an instrument of the foreign policy of the Republic of Korea
Keywords: SOCIAL SCIENCES::Social sciences::Political science; SOCIAL SCIENCES::Business and economics; HUMANITIES and RELIGION::History and philosophy subjects::Historical cultures; INTERDISCIPLINARY RESEARCH AREAS::Cultural heritage and cultural production; республіка Корея; поняття "м’яка сила"; Південна Корея; Україна; міжнародно-політичні дослідження; дипломатія; зовнішнья політика Південної Кореї; Republic of Korea; soft power; South Korea; Ukraine; international political studies; diplomacy; South Korean foreign policy